Posttraumatic stenosing tendovaginitis of the fourth extensor tendon compartment: a case report - Mayrhofer-Schmid, Maximilian; Harhaus-Wähner, Leila; Eisa, Amr (Archives of orthopaedic and trauma surgery, 2025)
While stenosing tendovaginitis of the first extensor tendon compartment is frequently encountered in hand surgical practice, similar pathologies in other extensor tendon compartments are rare and can, thus, be overlooked or misdiagnosed. This case report aims to point out the relevance and intricacies of these pathologies.
Gesehen am 04.12.2025